Visions of the future : chemistry and life science - Thompson, J. M. T. (Cambridge ; New York : Cambridge University Press, 2001)
Writing in a popular and well illustrated style, leading young scientists describe their research and give their visions of future developments in Chemistry and Life Science. The book conveys their excitement and enthusiasm and offers definitive reviews for anyone with a general interest in science.
Cover; Half-title; Title; Copyright; Contents; Preface; 1 Laser snapshots of molecular motions; 2 Enzymology takes a quantum leap forward; 3 World champion chemists: people versus computers; 4 Chemistry on the inside: green chemistry in mesoporous materials; 5 Diamond thin films: a twenty-first century material; 6 The secret of Nature s microscopic patterns; 7 Skeletal structure: synthesis of mechanics and cell biology; 8 The making of the virtual heart; 9 Exploring human organs with computers; 10 Reverse engineering the human mind; Contributor biographies; Index.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Chemistry; Life sciences; Chemistry; Biological Science Disciplines; Chimie; Sciences de la vie; chemistry; biological sciences; SCIENCE -- Chemistry -- General; Life sciences; Chemistry; Chemistry; Life sciences